Students’ perception on studying TOEFL using Yanto Tanjung’s YouTube channel - Hustarna; Sila Aprilia, Lausa; Fajaryani, Nunung (Research and Innovation in Language Learning, 2025)
This study aims to explore the perceptions of English students regarding their learning of the structure and written expression sections of the TOEFL test through Yanto Tanjung’s YouTube channel. This study employed a descriptive qualitative design, involving four participants selected through purposive sampling, and the data were collected using semi-structured interviews, which were then analyzed thematically. The findings revealed that students held a positive perception of Yanto Tanjung’s YouTube channel as a supplementary learning resource. The channel was perceived as beneficial in enhancing their understanding of complex grammar structures, improving test readiness, and fostering learning motivation. Participants appreciated the flexibility of self-paced learning, the clarity of explanations, and the relevance of examples provided in the videos. Furthermore, YouTube was regarded as an effective and accessible alternative for students who were unable to join formal TOEFL preparation courses. However, some challenges were also identified, including technical issues and limited access to exclusive content. In conclusion, Yanto Tanjung’s YouTube channel serves as a valuable support in TOEFL preparation, particularly in mastering structure and written expression, and highlights the potential of digital platforms to enhance students’ learning experiences and complement conventional instruction in the digital era.